The Use of Cloth Face Mask during the Pandemic Period in Indonesian People - Yudhastuti, Ririh (Kesmas, 2020)
The use of masks protects individuals from the spread of COVID-19 and control the source of transmission through droplets, but with limited medical masks, a cloth face mask can be used as an alternative personal protection from COVID-19. This study aimed to describe the use of cloth face mask as an alternative personal protection during the pandemic. WHO recommends the use of non-medical masks both at home and in public places. The use of face masks is a WHO’s recommendation on April 6, 2020. Medical masks are categorized as medical waste, then the disposal must be appropriate to prevent COVID-19 transmission in community. Cloth face mask can be used repeatedly and washed, its use can be adjusted to face. However, using a face mask alone is not enough to provide an adequate protection level. Other steps must be taken, such as washing hands with hand soap in running water, keeping a physical distance of minimum one meter from people, especially from those showing respiratory tract symptoms (coughing, sneezing), cleaning items touched by hands of people such as door handles and handles stairs. Therefore, the use of cloth face mask must be carried out together with clean and healthy living behaviors.